Guidance and outreach for inactive and unemployed : Germany - Huismann, Adrienne [Verfasser]; Hippach-Schneider, Ute [Mitarbeiter] (BIBB (Cedefop ReferNet Germany), 2018)
"Many countries across the European Union (EU) have high levels of unemployment and of inactive adults. These phenomena are frequently associated with low levels of qualification and insufficient basic skills. They may also reflect lack of adjustment between skills demanded in the labour market and skills developed in formal education and training. In both cases up-skilling and reskilling solutions could be explored to increase the employability of adults. The national reports developed by ReferNet partners reflect efforts done by Member States to reach vulnerable groups affected by unemployment and inactivity and help them reengage in learning and employment. The reports refer, in particular, to measures which may include young adults not in employment, education or training (NEET) and adults undergoing long term unemployment (LTU), given their persistence in many countries and the high challenges these groups face." (Excerpt, BIBB-Doku)
Keywords: G 1.2.2.4 Arbeitslosigkeit; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 1.3.6 Nachqualifizierung; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; Junger Erwachsener; Arbeitsloser; Langzeitarbeitslosigkeit; Nachqualifizierung; Bildungsberatung; Qualifizierungsmaßnahme; Bundesrepublik Deutschland